Strategi Kepala Sekolah dalam Meningkatkan Daya Saing Sekolah (Studi Multi Situs di SD Islam an-Nur dan SDIQu al-Bahjah Karangrejo) - Mochamad Hermanto (Matan : Journal of Islam and Muslim Society, 2021)
Abstract: The birth of new educational institutions resulted in schools competing to show their existence. Quality schools that are responsive to the dynamics of education and the needs of the community will be able to survive and exist in the world of education. For that, we need an appropriate step, to increase the competitiveness of schools. This study aims to determine the strategy formulation, implementation, and evaluation conducted by the principal to increase competitiveness in SD Islam an-Nur and SDIQu al-Bahjah. This study used a qualitative approach with a multi-site study research type. The collected data are analyzed individually through the process of reduction, data presentation, and drawing temporary conclusions, then cross-site data analysis is carried out. The results of this study indicate that the principal's strategy formulation in increasing competitiveness is fostering commitment in each component of the school, increasing the competence and motivation of school human resources, increasing student motivation and learning achievement, and promoting the community. Implementing the principal's strategy to increase competitiveness is all school components are involved in implementing the principal's strategy the commitment of the school component is to achieve the vision and mission of the school, full implementation of school activity programs supervised by the internal school. The evaluation carried out by the principal to increase competitiveness is conducting continuous supervision, establishing effective communication and coordination in implementing each activity program.